2013
DOI: 10.9790/487x-1366274
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Disaster Management between Japan & India

Abstract: Natural Calamity is a bitter truth from which no one can escape. So many deaths, diseases, economic and social loss are few results of natural calamity. Disaster risk is on the rise all the way through the world. The economic losses and the number of people who have been affected by natural calamities have increased significantly over the past decades than the population growth, which slows down the economic growth of the affected country. The physical, social, particularly the emotional aspect and economic lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The DRM practices in Bucharest, Mexico and Istanbul regarding legislation, planning, financial resources, organisational structures, risk assessment, early warning, education, training and research to investigate the risk assessment plans are considered in [45]. Similarly, Banerji et al [46] compared practices in Japan and India, and a comparison of seven megacities is presented in [47]. These last two studies examine the legal, policy, planning and institutional components to guide the comparison.…”
Section: Related Researchmentioning
confidence: 99%
“…The DRM practices in Bucharest, Mexico and Istanbul regarding legislation, planning, financial resources, organisational structures, risk assessment, early warning, education, training and research to investigate the risk assessment plans are considered in [45]. Similarly, Banerji et al [46] compared practices in Japan and India, and a comparison of seven megacities is presented in [47]. These last two studies examine the legal, policy, planning and institutional components to guide the comparison.…”
Section: Related Researchmentioning
confidence: 99%
“…Prior to the 2004 tsunami, the government apparatus in India had never expected that a tsunami could occur in such a large magnitude (Banerji and Singh 2013). It is also observed that pre-disaster mitigation and preparedness measures to deal with disasters of this scale were almost entirely non-existent in India (Minhans 2013).…”
Section: The Current State Disaster Risk Management In Indiamentioning
confidence: 99%
“…Despite the highest level of disaster preparedness by the Government of Japan, the impact of the disaster was huge. About 25,000 people lost their lives, 50,000 people were missing, 250,000 people were homeless, and the preliminary economic and human loss was estimated at US$310 billion (Banerji and Singh 2013). A pressing question is what would happen to India if a similar disaster were to hit the country.…”
Section: The Current State Disaster Risk Management In Indiamentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the challenges posed by the disasters have in a way forced the government to be more stringent on school safety norms and bring forth some regulatory reinforcements in schools. 9,10 The National Policy on Disaster Management, 2009 highlights the need for structural as well as non-structural safety in schools and educational institutions. The concepts of school safety and student's health are attaining priority in our country.…”
Section: Introductionmentioning
confidence: 99%